JNK inhibitor SP600125 is a partial agonist of human aryl hydrocarbon receptor and induces CYP1A1 and CYP1A2 genes in primary human hepatocytes - Dvorak, Zdenek; Vrzal, Radim; Henklova, Pavla; Jancova, Petra; Anzenbacherova, Eva; Maurel, Patrick; Svecova, Lucie; Pavek, Petr; Ehrmann, Jiri; Havlik, Roman; Bednar, Petr; Lemr, Karel; et al. (Biochemical pharmacology, 2008)
SP600125, a specific inhibitor of c-Jun-N-Terminal kinase (JNK), was reported as a ligand and antagonist of aryl hydrocarbon receptor (AhR) [Joiakim A, Mathieu PA, Palermo C, Gasiewicz TA, Reiners Jr JJ. The Jun N terminal kinase inhibitor SP600125 is a ligand and antagonist of the aryl hydrocarbon receptor. Drug Metab Dispos 2003;31(11):1279-82]. Here we show that SP600125 is not an antagonist but a partial agonist of human AhR. SP600125 significantly induced CYP1A1 and CYP1A2 mRNAs in primary human hepatocytes and CYP1A1 mRNA in human hepatoma cells HepG2. This effect was abolished by resveratrol, an antagonist of AhR. Consistent with the recent report, SP600125 dose-dependently inhibited CYP1A1 and CYP1A2 genes induction by a prototype AhR ligand 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in human hepatocytes. Moreover, SP600125 displayed typical behavior of a partial agonist in HepG2 cells transiently transfected with a reporter plasmid containing two inverted repeats of the dioxin responsive element or with a plasmid containing 5'-flanking region of human CYP1A1 gene. SP600125 transactivated the reporter plasmids with EC(50) of 0.005 and 1.89 microM, respectively. On the other hand, TCDD-dependent transactivation of the reporter plasmids was inhibited by SP600125 with IC(50) values of 1.54 and 2.63 microM, respectively. We also tested, whether the effects of SP600125 are due to metabolism. Using liquid chromatography/mass spectrometry approach, we observed formation of two minor monohydroxylated metabolites of SP600125 in human hepatocytes, human liver microsomes but not in HepG2 cells. These data imply that biotransformation is not responsible for the effects of SP600125 on AhR signaling. In conclusion, we demonstrate that SP600125 is a partial agonist of human AhR, which induces CYP1A genes.
Keywords: hepatocyty; Gene Expression Regulation, Enzymologic; JNK Mitogen-Activated Protein Kinases; regulace genové exprese enzymů; inhibitory proteinkinas; Anthracenes; polychlorované dibenzodioxiny; lidé; receptory aromatických uhlovodíků; Cytochrome P-450 CYP1A1; kultivované buňky; jaterní mikrozomy; hmotnostní spektrometrie; Hepatocytes; JNK mitogenem aktivované proteinkinasy; anthraceny; Cells, Cultured; Receptors, Aryl Hydrocarbon; Cytochrome P-450 CYP1A2; Protein Kinase Inhibitors; cytochrom P-450 CYP1A1; Microsomes, Liver; Mass Spectrometry; cytochrom P-450 CYP1A2; Polychlorinated Dibenzodioxins; Humans